The Effect of Silicon Valley Bank's Bankruptcy on The Indonesian Stock Exchange - Handayanto, Arga Bhayangkara; Tahang, Rahmawansyah Andi (AFEBI Accounting Review, 2023)
The occurrence of bank failures can exert a substantial influence on worldwide stock markets, leading to disturbances within the financial system and influencing the confidence of investors. On March 10, 2023, Silicon Valley Bank (SVB) encountered a notable setback inside the expanding technological sector. In contrast to other scholarly investigations, this study aims to examine the repercussions of the collapse of the SVB on the financial sector in Indonesia by employing an event study methodology. The duration of the window period, sometimes referred to as the event window, is set at 7 days. A time frame of 200 days is employed for the purpose of estimating anticipated returns and deviations from the norm. The parametric t-test, specifically the paired sample test, was employed in our study. The results of our study indicate that the declaration of the Silicon Valley Bank Bankruptcy does not have any discernible impact on the Financial Sector in Indonesia. The aforementioned findings are consistent with the research conducted by Pandey et al. (2023), which suggests that the consequences of Silicon Valley Bank's failure were more significant in developed economies. The consequences of these findings are significant for investors seeking to efficiently manage risk.